Intercultural marketing and adaptation of global campaigns: a review of key theories and practices - Becari, Jonas (Revista JRG de Estudos Acadêmicos, 2025)
Intercultural marketing is a fundamental discipline for companies operating globally, as it involves adapting communication strategies to the cultural specificities of each market. This article reviews the main theories and practices related to the adaptation of global campaigns, highlighting concepts such as standardization versus adaptation, transcreation and the application of cultural dimensions in international advertising. Real-life cases are presented that illustrate the importance of cultural sensitivity in the effectiveness of campaigns and the challenges faced by brands in multicultural environments are discussed. The analysis also highlights the role of technology and artificial intelligence in the personalization of global messages, reinforcing the need to balance global consistency and local relevance for the success of campaigns